Foreign Direct Investment, Innovation, and Exports: Firm-Level Evidence from People's Republic of China, Thailand, and Philippines - Ganeshan Wignaraja (Asian Development Bank (ADB), 2008)
This paper examines the links between ownership, innovation, and exports in electronics firms in three late-industrializing developing countries (People's Republic of China, Thailand, and Philippines), drawing on recent developments in applied international trade and innovation and learning. Technology-based approaches to trade offer a plausible explanation for firm-level exporting behavior. The econometric results (using probit) confirm the importance of foreign ownership and innovation in increasing the probability of exporting in electronics. Higher levels of skills, managers' education, and capital also matter in the People's Republic of China as well as accumulated experience in Thailand. Furthermore, a technology index composed of technical functions performed by firms emerges as a more robust indicator of innovation than the research and development to sales ratio. Accordingly, technological effort in electronics in these countries mostly focuses on assimilating and using imported technologies rather than formal research and development by specialized engineers.
hdl:11540/2356
Keywords: 330; Auslandsinvestition; Technischer Fortschritt; Exportwirtschaft; Elektronikindustrie; China; Thailand; Philippinen